Socialization of Tofu Liquid Waste Management (Whey Tofu) Becomes Biogas as Alternative Energy Reserves in the Framework of Creating an Environmentally Friendly Industry - Nely Ana Mufarida; Orisanto Darma Setiawan (OJS Universitas Muhammadiyah Gresik, 2020)
Arya Jaya is a trading business that is engaged in making tofu. UD. Arya Jaya began operations in 2003, by Mrs. Siti Aisyah. UD. Arya Jaya is in Bukkolan Village RT.01 RW.01 Paowan Village / Panarukan District Situbondo Regency East Java Province. To run this business, Mrs. Siti Aisyah was assisted by 12 workers. At UD. Arya Jaya, so far the tofu wastewater has never been used and treated but has been discharged into the river. As a result, various cases of environmental pollution that make a negative impact on public health occur a lot. Community service activities are also intended to train and foster communities around the tofu industry and tofu entrepreneurs so that they have knowledge about the utilization of tofu liquid waste and can improve skills around 75% to process tofu liquid waste into biogas in processing tofu liquid waste into biogas so it is expected With good management of the waste produced by the tofu making industry, it will add value to the product and be more environmentally friendly. In addition, the management of tofu wastewater in a waste to product manner can efficiently cost the costs, materials used, and energy to make new products from waste raw materials. Besides that, entrepreneurs know that they will no longer be difficult to deal with their waste. Based on the situation analysis above, the PKM Team together with UD. Arya Jaya seeks to overcome the problem referred to as